Isolation and screening of pectinase producing bacteria - Geetananthini Mahalingam (2024)
Enzymes play a crucial role in various industrial processes, with pectinases being of particular significance due to their application in fruit juice extraction and waste treatment. However, the current sources of pectinase enzymes are often limited in yield and specificity, highlighting the need for exploration of novel microbial sources. The study's objectives encompass screening and isolating pectinolytic bacteria, measuring pectinase activity, and characterizing isolated strains through morphological and molecular studies. Soil, as a reservoir of diverse microbial communities, offers immense potential for biotechnological applications. In this thesis, we investigated soil microbial diversity and sought to identify strains capable of producing pectinase enzymes. Serial dilution techniques were employed to reduce microbial content, followed by screening on nutrient agar and subsequent selection of positive colonies on pectin agar. Morphological analysis identified six distinct strains, three gram-positive and three gramnegative, which were further characterized. Molecular identification involved overnight fermentation in LB broth, DNA extraction, and gel electrophoresis, revealing the genetic diversity of the selected strains. NanoDrop spectrophotometry was employed to evaluate DNA purity and concentration. The results showed variations in DNA concentration and purity ratios across the isolates. For instance, ST3 exhibited the highest concentration of DNA and the highest purity ratio, indicating a high amount of pure DNA in the sample. In contrast, ST10 displayed the lowest concentration of DNA and a negative purity ratio, suggesting potential contamination or issues with the sample. Pectinase activity was quantified using the DNS method, demonstrating the enzymatic potential of the isolated strains. Enzyme activity assays revealed variability among strains, with ST3 and ST13 demonstrating the highest pectinase activities. This study underscores the importance of soil microbes in biotechnological processes and provides valuable insights into the isolation and characterization of pectinase producing strains, and these results contribute to the identification of novel sources of pectinase enzymes, thereby advancing the development of efficient enzymatic processes in various industries